2021
DOI: 10.2337/db21-0077
|View full text |Cite
|
Sign up to set email alerts
|

Human Islet MicroRNA-200c Is Elevated in Type 2 Diabetes and Targets the Transcription Factor ETV5 to Reduce Insulin Secretion

Abstract: MicroRNAs (miRNAs) are part of deregulated insulin secretion in type 2 diabetes (T2D) development. Rodent models have suggested miR-200c to be involved, but the role and potential as therapeutic target of this miRNA in human islets is not clear. Here we report increased expression of miR-200c in islets from T2D as compared with non-diabetic (ND) donors and display results showing reduced glucose-stimulated insulin secretion in EndoC-βH1 cells overexpressing miR-200c. We identify transcription factor ETV5 as th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 34 publications
3
30
0
Order By: Relevance
“…However, the bulk of these studies are in model systems (e.g., animal models, cell lines), so our knowledge of miRNAs in human pancreatic islets (HPIs) remains limited. To date, most studies examining miRNA expression in HPIs have tested only a small number of miRNAs (25)(26)(27)(28). Of the two more comprehensive sequencing-based studies of HPI miRNAs (29,30), both have been limited in sample size (n≤7).…”
Section: Introductionmentioning
confidence: 99%
“…However, the bulk of these studies are in model systems (e.g., animal models, cell lines), so our knowledge of miRNAs in human pancreatic islets (HPIs) remains limited. To date, most studies examining miRNA expression in HPIs have tested only a small number of miRNAs (25)(26)(27)(28). Of the two more comprehensive sequencing-based studies of HPI miRNAs (29,30), both have been limited in sample size (n≤7).…”
Section: Introductionmentioning
confidence: 99%
“…However, the bulk of these studies are in model systems (e.g., animal models, cell lines), so our knowledge of miRNAs in human pancreatic islets (HPIs) remains limited. To date, most studies examining miRNA expression in HPIs have tested only a small number of miRNAs ( 25 28 ). Of the two more comprehensive sequencing-based studies of HPI miRNAs ( 29 , 30 ), both have been limited in sample size (n ≤ 7).…”
mentioning
confidence: 99%
“…Analysis of the ceRNA regulatory network associated with ETV5 indicated that ETV5 is regulated by miR-8067 in glioblastoma [ 122 ]. In human islets, the expression of ETV5 is correlated with miR-200c [ 123 ]. MiR-200c directly binds the 3′-untranslated terminal region (UTR) of ETV5 mRNA and reduces ETV5 expression, which decreased glucose-stimulated insulin secretion in type 2 diabetes [ 123 ].…”
Section: Dysregulation Of Etv5 Expressionmentioning
confidence: 99%
“…In human islets, the expression of ETV5 is correlated with miR-200c [ 123 ]. MiR-200c directly binds the 3′-untranslated terminal region (UTR) of ETV5 mRNA and reduces ETV5 expression, which decreased glucose-stimulated insulin secretion in type 2 diabetes [ 123 ]. Recently, it was demonstrated that miR-219 plays a critical role in central neuron system myelination and remyelination after injury [ 124 ].…”
Section: Dysregulation Of Etv5 Expressionmentioning
confidence: 99%